The Shannon Cipher System With a Guessing Wiretapper Eavesdroping Through a Noisy Channel - Haroutunian, Evgueni A.; Margaryan, Tigran M. (Mathematical Problems of Computer Science, 2021)
In this paper we study the processes in the Shannon cipher system with discrete memoryless source and a guessing wiretapper. The wiretapper observes a cryptogram of M-vector ciphered messages passed through the noisy channel and tries to guess the secret plaintext with length N. The security of encryption system is measured by the average number of guesses needed for the wiretapper to uncover the plaintext. The problem was suggested by Arikan and Merhav as a generalization of their result for noiseless channel to wairtapper.